Respuesta :

Neuron
If you would like to solve the equation -y + 56 = 167, you can calculate this using the following step:

-y + 56 = 167
-y = 167 - 56
-y = 111
y = -111

The correct result would be -111.
Well, forst you have to do the opposite to find what y equals. You have to start on the side with the variable. The opposite off adding is subtaction.

-y+56=167
-56.

-y+56=167
-56
What you do to one side you must do to the other, you mark out 56 and take 167-56.

That equals 111.

111=y

I hope this explains why! :)